Long-term projections of supply and demand for selected agricultural products in Iran - LeBaron, Allen; Mohtadi, Malek M.; Beutler, Ivan F. (Logan, Utah : Utah Agricultural Experiment Station, Utah State University, 1970)
This publication analyzes the results of a study of the long-term projections of supply and demand for selected agricultural products in Iran for the years 1975 and 1980. The objective of the research is to estimate import and export requirements of major crop and livestock products and the outlook for Iranian markets in 1975 and 1980.
Includes bibliographical references: p. 357-364.
rpm 01/02/2019
Loans
Keywords: Agricultural economics; Farm produce; Food supply; Food consumption; Iran